Extrajudicial Dispute Resolution in Handling Environmental Cases in Indonesia (Case Study: River Water Pollution by PT Sugar Labinta in South Lampung) - Fauzi, Dzulfikar Ahmad (Faculty of Law, Universitas Negeri Semarang, 2024)
This paper examines extrajudicial dispute resolution mechanisms utilized in addressing environmental cases in Indonesia, with a focus on a specific case involving the alleged pollution of river water by PT Sugar Labinta in South Lampung. It delves into the legal frameworks, stakeholder engagement processes, and outcomes of extrajudicial dispute resolution efforts in environmental matters. Drawing on a case study approach, the paper analyzes the effectiveness and challenges of extrajudicial mechanisms in resolving environmental disputes, particularly in cases of alleged pollution by industrial entities. It explores the roles of various stakeholders, including government agencies, industry representatives, affected communities, and non-governmental organizations, in the resolution process. Furthermore, the paper evaluates the implications of extrajudicial dispute resolution on environmental protection, legal accountability, and community rights. It examines the extent to which such mechanisms contribute to the realization of environmental justice, sustainable development, and corporate responsibility in Indonesia. In conclusion, the paper offers insights into the strengths and limitations of extrajudicial dispute resolution in handling environmental cases, using the PT Sugar Labinta case as a lens. It suggests recommendations for improving the effectiveness and fairness of extrajudicial mechanisms, enhancing transparency, accountability, and community participation in environmental decision-making processes.